Vitamin D in Human Immunodeficiency Virus Infection: Influence on Immunity and Disease - Jiménez-Sousa, María Ángeles; Martínez, Isidoro; Medrano, Luz María; Fernández-Rodríguez, Amanda; Resino, Salvador (Frontiers in Immunology, 2018)
People living with human immunodeficiency virus (HIV) infection typically have hypovitaminosis D, which is linked to a large number of pathologies, including immune disorders and infectious diseases. Vitamin D is a key regulator of host defense against infections by activating genes and pathways that enhance innate and adaptive immunity. Vitamin D mediates its biological effects by binding to the vitamin D receptor (VDR), and activating and regulating multiple cellular pathways. Single nucleotide polymorphisms (SNPs) in genes from those pathways have been associated with protection from HIV-1 infection. High levels of vitamin D and VDR expression are also associated with natural resistance to HIV-1 infection. Conversely, vitamin D deficiency is linked to more inflammation and immune activation, low peripheral blood CD4+ T-cells, faster progression of HIV disease and shorter survival time in HIV-infected patients. Vitamin D supplementation and restoration to normal values in HIV-infected patients may improve immunologic recovery during combination antiretroviral therapy, reduce levels of inflammation and immune activation, and increase immunity against pathogens. Additionally, vitamin D may protect against the development of immune reconstitution inflammatory syndrome (IRIS) events, pulmonary tuberculosis, and mortality among HIV-infected patients. In summary, this review suggests that vitamin D deficiency may contribute to the pathogenesis of HIV infection. Also, vitamin D supplementation seems to reverse some alterations of the immune system, supporting the use of vitamin D supplementation as prophylaxis, especially in individuals with more severe vitamin D deficiency.